Smartphone Addiction and Awareness of University Students During the Pandemic Period: The Case of Bitlis Eren University - Mustafa Agah Tekindal; Barış Çağırkan (Yeni Medya, 2022)
Smartphone addiction, known as a fear of being without a mobile phone, is often discussed with an Internet overuse problem or addiction. But in general, it is rarely the phone itself that creates the addiction, but rather the games, apps, and online worlds it connects people to. This study aims to measure the level of smartphone addiction in university students living in Eastern Turkey and identify the university students’ smartphone addiction and awareness during the COVID-19 pandemic. The study population consists of 443 students who were studying in different departments in the 2020-2021 spring term at Bitlis Eren University. To summarise the key findings, it has been observed that men are more smartphone-addicted than women. Those who do not think that the duration of smartphone use has increased during the COVID-19 pandemic period has more impact on the SAS than those who do. It has been observed that students in the 1st grade are more phone addicted than those in the 2nd grade. Those who used the smartphone for 1 year or less were more likely than those who used it for 1 year or less were more smartphone addicts than those who used it for 5 years or more.